Pendampingan Pastoral Konseling Kepada Istri yang Ditinggalkan Suami di GMIST Yerusalem Enemawira - Agrendi Mangali; Joshua Tuerah; Meidy Sumeleh (PT. Giat Konseling Nusantara, 2025)
ABSTRACT Family life certainly requires a harmonious and happy life. However, the journey of life is sometimes not as expected. What we cannot deny is that there are married couples who separate and end in divorce. So that wives who are left by their husbands will try to survive while taking care of the children left by their fathers. In this paper, the researcher describes the burden of wives when they are left by their husbands, analyzes the causes of separation and also offers several solutions to prevent and overcome through pastoral counseling services using descriptive qualitative methods. Keywords: Pastoral Counseling, Wife, Pastoral Counseling Handling